Synthesis of 6,6-Dimethyl-2-Cyclopentadienylethylbicyclo[3.1.1] Hept-2-Ene and of 6,6-Dimethyl-2-Indenylethylbicyclo[3.1.1] Hept-2-Ene. (Global Journal of Science Frontier Research, 2013)
The new compounds 6,6-dimethyl-2-cyclopentadienylethylbicyclo[3.1.1] hept-2-ene (4) and 6,6-dimethyl-2-indenylethylbicyclo[3.1.1] hept-2-ene (5) were synthesized in 82% and 60% yield respectively using 6,6-dimethyl-2-p-toluenesulphonyloxomethylbicyclo[3.1.1] hept-2-ene (2). However, compounds -(4) and (5) were obtained in 71% and 81% yield respectively using 6,6-dimethyl-2-sulphonyloxomethylbicyclo[3.1.1] hept-2-ene (3). All compounds were characterized by NMR, Infra-red, Micro Analysis and Mass Spectroscopy.
Keywords: ligand; metallocene; cyclopentadienyl; indenyl; organ metallic; n-buthyllithium